Relationship of Maqasid al-Shari’ah with Usul al-Fiqh (overview of historical, methodological and applicative aspects) - Nur Hasan (Sultang Agung Islamic University, 2020)
Studies on maqasid al-shari‘ah have been widely written and reviewed by researchers of Islamic law. Some have written about the maqasid al-shari‘ah’s concept, the figures’ thought, and its application to various Islamic law and social issues. As a new study, maqasid al-shari‘ah is widely studied in the context of renewing Islamic law, however little discuss about history of maqasid al-shari‘ah and relations with usul al-fiqh. Because historically, the birth of maqasid al-shari‘ah can’t be separated from development of usul al-fiqh through the scholars usul al-fiqh. As well as in terms of methodology, maqasid al-shari‘ah have a close relationship with method istinbāṭ al-Éhkām in usul al-fiqh, as qiyās, maslahāh al-mursālah, al-ÐarīÑah and istihsān. While in terms of application, maqasid al-shari‘ah together with usul al-fiqh namely departing from the proposition of naqlī (revelation) and Ñaqlī (reason) which is global and analyzes various opinions in deciding Islamic law. It’s just that usul al-fiqh is dominated by linguistic aspects, meanwhile the maqasid al-shari‘ah emphasizes the divine aspect behind the law. That’s why to see relationships among maqasid al-shari‘ah and usul al-fiqh, this research uses library research method or literature review by researching the main sources which discusses about relations maqasid al-shari‘ah and usul al-fiqh in terms of historical, methodological and applicative.